Novel Therapeutic Targets in Cutaneous Squamous Cell Carcinoma - Yanagi, Teruki; Kitamura, Shinya; Hata, Hiroo (Frontiers in Oncology, 2018)
Cutaneous squamous cell carcinoma (SCC) is one of the common cancers in Caucasians, accounting for 20-30% of cutaneous malignancies. The risk of metastasis is low in most patients; however, aggressive SCC is associated with very high mortality and morbidity. Although cutaneous SCC can be treated with surgical removal, radiation and chemotherapy singly or in combination, the prognosis of patients with metastatic SCC is poor. Recently, the usage of immune checkpoint blockades has come under consideration. To develop effective therapies that are less toxic than existing ones, it is crucial to achieve a detailed characterization of the molecular mechanisms that are involved in cutaneous SCC pathogenesis and to identify new drug targets. Recent studies have identified novel molecules that are associated with SCC carcinogenesis and progression. This review focuses on recent advances in molecular studies involving SCC tumor development, as well as in new therapeutics that have become available to clinicians.